2024
DOI: 10.3389/fmicb.2024.1404673
|View full text |Cite
|
Sign up to set email alerts
|

The causal role of gut microbiota in susceptibility of Long COVID: a Mendelian randomization study

Zuming Li,
Qinghua Xia,
Jieni Feng
et al.

Abstract: BackgroundLong COVID is a major challenge facing the public. Gut microbiota is closely related to Long COVID. However, the causal effects between gut microbiota and Long COVID remains unclear.MethodsUsing summary statistics from Genome-Wide Association Studies (GWAS), Mendelian randomization (MR) analyses were performed to investigate the relationship between gut microbiota and Long COVID. The primary statistical method employed was Inverse Variance Weighted (IVW). Sensitivity analyses were then conducted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Research conducted by Ghoshal and Ghoshal [48] suggest that individuals who have been affected by Long COVID have a higher likelihood of developing irritable bowel syndrome when compared to normal volunteers. A study utilizing Mendelian randomization demonstrated that various taxa of gut microbiota may potentially play a causal role in the development of Long COVID [49]. A separate study conducted by Su et al [50] revealed the presence of distinct gut-microbiome enterotypes in individuals with Long COVID and its associated symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Ghoshal and Ghoshal [48] suggest that individuals who have been affected by Long COVID have a higher likelihood of developing irritable bowel syndrome when compared to normal volunteers. A study utilizing Mendelian randomization demonstrated that various taxa of gut microbiota may potentially play a causal role in the development of Long COVID [49]. A separate study conducted by Su et al [50] revealed the presence of distinct gut-microbiome enterotypes in individuals with Long COVID and its associated symptoms.…”
Section: Discussionmentioning
confidence: 99%